Human thermoregulation and the cardiovascular system - Gonzalez-Alonso, J. (Experimental Physiology, 2012)
A key but little understood function of the cardiovascular system is to exchange heat between the internal body tissues, organs and the skin to maintain internal temperature within a narrow range in a variety of conditions that produce vast changes in external (exogenous) and/or internal (endogenous) thermal loads. Heat transfer via the flowing blood (i.e. vascular convective heat transfer) is the most important heat-exchange pathway inside the body. This pathway is particularly important when metabolic heat production increases many-fold during exercise. During exercise typical of many recreational and Olympic events, heat is transferred from the heat-producing contracting muscles to the skin surrounding the exercising limbs and to the normally less mobile body trunk and head via the circulating blood. Strikingly, a significant amount of heat produced by the contracting muscles is liberated from the skin of the exercising limbs. The local and central mechanisms regulating tissue temperature in the exercising limbs, body trunk and head are essential to avoid the deleterious consequences on human performance of either hyperthermia or hypothermia. This brief review focuses on recent literature addressing the following topics: (i) the dynamics of heat production in contracting skeletal muscle; (ii) the influence of exercise and environmental heat and cold stress on limb and systemic haemodynamics; and (iii) the impact of changes in muscle blood flow on heat exchange in human limbs. The paper highlights the need to investigate the responses and mechanisms of vascular convective heat exchange in exercising limbs to advance our understanding of local tissue temperature regulation during exercise and environmental stress.